Childhood Adversity Linked to Neurological Circuitry Changes and Mental Health Disorders. Narrative Review - Alexander L. Shand (University Library System, University of Pittsburgh, 2021)
Children who experience adversity have increased risk for psychiatric disorders. However, little is known about the exact alterations that occur in the neural circuitry and how that information may help lead to early diagnosis or preventive medicine. Research has shown that there are specific changes in neurological functional connectivity in the brain associated with childhood adversity. This review will examine recent papers that have investigated the correlation between these changes in brain connectivity and specific psychiatric disorders. Understanding the changes may help with preventive medicine by ensuring clinicians monitor patients with more severe history of adversity who are therefore at higher risk for developing a psychiatric disorder. This paper will also address potential recommendations that could be implemented in the future as research offers more conclusive evidence. Research is now beginning to address the questions of whether these changes can be attenuated, either during childhood or as adults.